1993
DOI: 10.1002/humu.1380020407
|View full text |Cite
|
Sign up to set email alerts
|

Screening for TP53 mutations in osteosarcomas using constant denaturant gel electrophoresis (CDGE)

Abstract: We have previously developed conditions to screen for TP53 point mutations inside the conserved domains II-V of the gene by using constant denaturant gel electrophoresis (CDGE). The present study reports conditions for screening more of the codons in the frequently mutated region exon 5-8 and for detecting mutations in sequences encoding functional domains in the N- and C-terminal part of the protein. The ability of the CDGE technique to detect mutations was studied using controls with known sequence deviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 43 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…These similarities in taxonomic affinity, but differences in gel position, indicate that DGGE was able to detect genetic differences that may relate to species-or strain-level variation that would normally be impossible to identify using traditional methods. It is possible that in our evaluation of the DGGE sequences we have missed some of the sequence information that could account for the difference in gel position, because the length of sequence that we were able to recover from the bands varied (from 105 to 237 bases out of approximately 250 total bases) and even a single base difference can result in the distinct separation of two bands by DGGE (30).…”
Section: Dgge Analysismentioning
confidence: 99%
“…These similarities in taxonomic affinity, but differences in gel position, indicate that DGGE was able to detect genetic differences that may relate to species-or strain-level variation that would normally be impossible to identify using traditional methods. It is possible that in our evaluation of the DGGE sequences we have missed some of the sequence information that could account for the difference in gel position, because the length of sequence that we were able to recover from the bands varied (from 105 to 237 bases out of approximately 250 total bases) and even a single base difference can result in the distinct separation of two bands by DGGE (30).…”
Section: Dgge Analysismentioning
confidence: 99%
“…Not surprisingly, it was reported that p53 is deleted or mutated in the majority of cancers. Experiments involving p53 knockout mice have shown that the occurrence of tumors increases with the loss of p53 function [26,27]. In some cases inactivation of p53 involves small changes such as point mutations [28][29][30].…”
Section: Exploitation Of Protein Profiling In Leukemia Researchmentioning
confidence: 99%
“…All the conditions and PCR primers (shown in Figure 1) for CDGE have been described previously (B0rresen et al, 1991;Smith-S0rensen et al, 1993;Andersen et al, 1995). A specific analysis was made to identify a frequently described G to C mutation in codon 156.…”
Section: Loss Of Heterozygosity (Loh)mentioning
confidence: 99%